Research on information channel characteristics of a ship electric power system - Mahmoud, M. S. Alsuod; Ushkarenko, Oleksandr; Dorogan, Olga (My University, 2018)
Abstract. This article deals with the developed methodology of research information flows in the distributed control system network of a ship electric power system, based on the notion of software structure in the form of pattern network, in which each generator is assigned to a particular software object, and communication relations represent different types of information interactions between objects. Using the queuing and pattern theories gave the opportunity to develop the algorithm of software formal reorganization in the context of reduction system’s response time.
Mahmoud, M. Al-Suod. Research on information channel characteristics of a ship electric power system / M. Al-Suod Mahmoud, O. Ushkarenko, O. Dorogan // Przegląd Elektrotechniczny. – 2018. – № 6. – P. 19–26.
Keywords: power plant; Information flows; Pattern network; Request queue